A Mutual Parody of Meaning in Circus Clown and Ethnographic Discourse - Little, Kenneth (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1991)
This article traces some of the conversations between a European circus clown named Pipo and myself in order to draw out the characteristics of intertextuality that I argue are key features of the ethnographic endeavour. Central to our conversations was a concern with our mutual productions of identity as clown artist and ethnographer. I explore how ambiguous, parodic, and subversive such productions can be. Along the way Pipo taught me a few good jokes and something of how to tell them and I try them out on modernist anthropology in an effort to make this “body” of knowledge/power parodic.